A comparative review of aging and B cell function in mice and humans - Scholz, Jean L; Diaz, Alain; Riley, Richard L; Cancro, Michael P; Frasca, Daniela (Current opinion in immunology, 2013)
•B cell generation in bone marrow declines with age in mice but may be maintained in humans.•Shifts in naïve and antigen-experienced peripheral B cell subsets are now well documented in both mice and humans, although some controversies still exist in humans.•Antibody responses to both T cell-dependent (TD) and T cell-independent (TI) antigens are generally dampened with age in both species.•Further work in mice will inform additional studies to be done in humans, affording identification of predictors of the antibody response to antigens as well as molecular targets for improving vaccine efficacy. Immune system function declines with age. Here we review and compare age-associated changes in murine and human B cell pools and humoral immune responses. We summarize changes in B cell generation and homeostasis, as well as notable changes at the subcellular level; then discuss how these changes help to explain alterations in immune responses across the adult lifespan of the animal. In each section we compare and contrast findings in the mouse, arguably the best animal model of the aging immune system, with current understanding of B cell immunity in humans